(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
Psychology as a field of knowledge receives an important problematization from the text What is psychology? by the French philosopher Georges Canguilhem (1904-1995). His criticism is strengthened when we consider the concept of life explored by the author, that is, as something precarious and errant. Thus, an epistemic impasse in psychology is revealed: the fragility of apprehending the living as creator of norms, given its essential precariousness. Psychology, by ignoring the understanding of life in these terms suggested by Canguilhem, turns the psychologist into an instrument at the service of the pathologization of the singular forms of existence.